High performance sensorless vector control of induction motor drives - Blasco Giménez, Ramón (1995)
The aim of this research project was to develop a vector controlled induction motor drive operating without a speed or position sensor but having a dynamic performance comparable to a sensored vector drive. The methodology was to detect the motor speed from the machine rotor slot harmonics using digital signal processing and to use this signal to tune a speed estimator and thus reduce or eliminate the estimator’s sensitivity to parameter variations. Derivation of a speed signal from the rotor slot harmonics using a Discrete Fourier Transform-based algorithm has yielded highly accurate and robust speed signals above machine frequencies of about 2 Hz and independent of machine loads. The detection, which has been carried out using an Intel i860 processor in parallel with the main vector controller, has been found to give predictable and consistent results duing speed transient conditions. The speed signal obtained from the rotor slot harmonics has been used to tune a Model Reference Adaptive speed and flux observer, with the resulting sensorless drive operating to steady state speed accuracies down to 0.02 rpm above 2 Hz (i.e. 60 rpm for the 4 pole machine). A significant aspect of the research has been the mathematical derivation of the speed bandwidth limitations for both sensored and sensorless drives, thus allowing for quantitative comparison of their dynamic performance. It has been found that the speed bandwidth limitation for sensorless drives depends on the accuracy to which the machine parameters are known and that for maximum dynamic performance it is necessary to tune the flux and speed estimator against variations in stator resistance in addition to the tuning mechanism deriving from the DFT speed detector. New dynamic stator resistance tuning algorithms have been implemented. The resulting sensorless drive has been found to have a speed bandwidth equivalent to sensored drives fitted with medium resolution encoders (i.e. about 500 ppr), and a zero speed accuracy of ± 8 rpm under speed control. These specifications are superior to any reported in the research literature.